2005
DOI: 10.1300/j452v07n02_01
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Convention and Meeting Management Research 1990–2003

Abstract: The growing importance of the convention and meeting sector provided the impetus for this review of research directions and the structure of the convention and meeting field. A total of 137 convention articles published in major hospitality and tourism journals from 1990 to 2003 were collected and content-analyzed for research method and subject. Specifically, articles were categorized based on (a) nature of article, (b) research design, (c) statistical technique, (d) research focus, and (e) functional area. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 23 publications
3
31
0
Order By: Relevance
“…The research includes studies on economic impact of conventions (e.g., Crouch & Ritchie, 1998;Rutherford & Kreck, 1994) and association meeting planners' site selection process (e.g., Baloglu & Love, 2001;Oppermann, 1996). Less attention has been paid to individual convention attendees and their wants and needs (Lee & Back, 2005;Mair & Thompson, 2009;Zhang, Leung, & Qu, 2007).…”
Section: Meeting Attendee Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…The research includes studies on economic impact of conventions (e.g., Crouch & Ritchie, 1998;Rutherford & Kreck, 1994) and association meeting planners' site selection process (e.g., Baloglu & Love, 2001;Oppermann, 1996). Less attention has been paid to individual convention attendees and their wants and needs (Lee & Back, 2005;Mair & Thompson, 2009;Zhang, Leung, & Qu, 2007).…”
Section: Meeting Attendee Behaviormentioning
confidence: 99%
“…Tanford, Montgomery, and Nelson (2011), however, argued for surveying attendees while experiencing an event rather than after the event. Research related to satisfaction in the meetings and convention industry has been applied mainly to meeting planners' destination choice (Baloglu, Pekcan, Chen, & Santos, 2003;Bauer, Law, Tse, & Weber, 2008;Dragi cevi c, Stankoc, Armenski, & Stetic, 2011;Lee & Back, 2005;Yoo & Weber, 2005) and the attendee's satisfaction with the event (Bauer et al, 2008;Lu & Cai, 2011;Tanford et al, 2011). For the latter, a variety of approaches have been adopted to explain the measurement of satisfaction (Spreng, MacKenzie, & Olshavsky, 1996).…”
Section: Conference Satisfactionmentioning
confidence: 99%
“…Subsequently, the methodology for A number of writers in recent years have placed a spotlight upon the prevailing themes and topics focused upon by event scholars (Getz, 2009;Mair & Whitfield, 2013). Yet, other than Lee and Back (2005), who looked specifically at convention and meeting research methods from 1990 to 2003, there has been an absence of work that looks at the dominant research methods. Indeed, Mair and Whitfield (2013) conclude by acknowledging the value of future work that focuses on the research methods employed by event scholars.…”
Section: Review Of Established Methods In Event Researchmentioning
confidence: 99%
“…Globally, business travel is predicted to grow at an annual rate of 3.6% to the year 2019 and account for expenditures in excess of US$1376 billion (WTTC, 2009). Business travel activity is a major contributor to the economic development of many regions, cities and countries (Crouch and Ritchie, 1998; Kim et al , 2003; Lee and Back, 2005). Business tourism may be defined as being ‘concerned with people travelling for purposes which are related to their work.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consistent with this approach, MICE travellers are defined as ‘people who undertake personal or employer funded trips to attend meetings, incentives, conventions and exhibitions, both at home and overseas’. Researchers have indicated that business travel benefits many regions and countries by providing higher levels of income, employment and government revenue (Crouch and Ritchie, 1998; Kim et al , 2003; Lee and Back, 2005). During the last quarter of the twentieth century, the fast‐growing Asia‐Pacific region became recognized as one of the most attractive destinations for marketers (WTO, 1998) with approximately 356 million international trips being made to destinations within the region in 2006.…”
Section: Literature Reviewmentioning
confidence: 99%